Eksistensi Peraturan Nagari Dalam Sistem Hukum di Indonesia - Desip Trinanda (Faculty of Law, Andalas University, 2022)
This study is a study of the existence of Nagari Regulations (Perna) in the legal system in Indonesia. Perna is a form of delegation from Law Number 6 of 2014 concerning Villages. However, Perna is not listed in Law No. 12 of 2011 concerning the Establishment of Legislation. This study is a normative legal research with a statutory and conceptual science approach. The results of this study indicate that the existence of Perna does not have a clear legal basis after the enactment of Law no. 12 of 2011. The reason is that the Perna which is a regulation at the level of a village regulation has been issued in the hierarchy of laws and regulations. That is why, if the a Perna conflicts with higher regulations or the public interest, it cannot be tested through the Supreme Court as the institution which is authorized to examine statutory regulations under the law against the law. In addition, Perna also experiences weaknesses in terms of law enforcement, which is carried out by Parik Paga Nagari (Nagari Law Enforcement Agency) which basically does not provide a solution to the enforcement of Perna, but could create new problems in the community.